let K be Field; :: thesis: for M1, M2 being Matrix of K st len M1 = len M2 & width M1 = width M2 holds

M1 = M1 - (M2 - M2)

let M1, M2 be Matrix of K; :: thesis: ( len M1 = len M2 & width M1 = width M2 implies M1 = M1 - (M2 - M2) )

assume ( len M1 = len M2 & width M1 = width M2 ) ; :: thesis: M1 = M1 - (M2 - M2)

then A1: M1 - (M2 - M2) = M1 - (0. (K,(len M1),(width M1))) by Th2

.= M1 + (0. (K,(len M1),(width M1))) by Th9 ;

M1 = M1 - (M2 - M2)

let M1, M2 be Matrix of K; :: thesis: ( len M1 = len M2 & width M1 = width M2 implies M1 = M1 - (M2 - M2) )

assume ( len M1 = len M2 & width M1 = width M2 ) ; :: thesis: M1 = M1 - (M2 - M2)

then A1: M1 - (M2 - M2) = M1 - (0. (K,(len M1),(width M1))) by Th2

.= M1 + (0. (K,(len M1),(width M1))) by Th9 ;